HOME INDUSTRI PENGOLAHAN SAGU SEBAGAI MAKANAN OLEH IBU RUMAH TANGGA DI SELATPANJANG KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Okmalia, Tanti Ana; Natuna, Daeng Ayub; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:The purpose of this research is to know the life skill to process sago as food by housewife in Strait of Tebing Tinggi District of Meranti Island viewed from (1) personal skill (2) social skills (3) vocational skills and (4) academic skill. This research is descriptive research using qualitative approach. This qualitative method is used because of several considerations. First, adjusting qualitative methods is easier when dealing with double reality; Second, this method presents directly the nature of the relationship between the researcher and the respondent; Third, this method is more sensitive and more adaptable to the many sharpening of mutual influences and to the pattern of values encountered. Given the wide scope of the problem, the authors need to provide limitations of the problem to be studied ie on life skill to process sago as food by housewives in the long districts high cliffs Meranti archipelago district. The problem formulation in this research is